Application method of multi-active-point pyrenyl fused ring compound in primary battery

By using multi-active dot pyrene-yl fused ring compound as the positive electrode material of lithium primary battery, combined with in-situ carbon load and polyhydroxyproton additives, the problems of low energy density and insufficient safety of lithium primary battery are solved, and battery performance with high energy density and excellent safety are achieved.

CN119864417AActive Publication Date: 2025-04-22NANKAI UNIV +1

Patent Information

Application Number
CN202510054606.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing lithium primary battery positive electrode materials have problems such as low energy density, relatively low working voltage, high production cost, high toxicity, increased safety, easy dissolution of organic molecules, and poor conductivity.

Method used

Multi-active dot pyrene-yl fused ring compound is used as the positive electrode active material, and the number of functional groups is regulated by changing the reaction conditions, the π-π effect is enhanced, the material conductivity is improved, and the battery performance is improved through in-situ carbon loading and the introduction of solid and liquid polyhydroxyl groups for proton additives.

Benefits of technology

The energy density of lithium primary batteries has been significantly improved, reaching more than 1400mAh/g and more than 3600Wh/kg, improving safety and electrical conductivity, and reducing raw material costs and realizing the possibility of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864417A_ABST
    Figure CN119864417A_ABST
Patent Text Reader

Abstract

The invention provides an application method of a multi-active-point pyrenyl fused ring compound in a primary battery, which comprises the following steps: preparing a positive electrode by taking the multi-active-point pyrenyl fused ring compound as a positive electrode active material, and assembling the primary battery by taking alkali metal as a negative electrode and an alkali metal salt solution as electrolyte. The performance of the multi-active-site organic positive electrode material in a primary battery is greatly improved through active substance in-situ carbon loading, a solid polyhydroxy proton donor additive and a liquid proton donor additive. The organic matter is used as a positive electrode, alkali metal is used as a negative electrode, an alkali metal salt solution is used as electrolyte, multi-electron reduction of organic functional groups can be realized in a battery, and the specific capacity and the energy density of the organic electrode material are greatly improved. The organic positive electrode material has the advantages of high energy density, low cost, easiness in large-scale production and the like, and has high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of organic positive electrode materials for batteries, and in particular relates to an application of a condensed-ring organic material with multiple active points in the field of primary batteries and a method for improving its performance. Background Art

[0002] Today's society has an increasingly urgent demand for new energy structures. In the new energy system, batteries have become the key to the development of many fields such as new energy vehicles and large-scale energy storage. As an important branch of lithium batteries, lithium primary batteries have the advantages of high energy density, high operating voltage, long storage life and wide operating temperature range. They have been widely used in aerospace, military, medical, transportation, people's livelihood and other aspects. With the unknown fields such as military equipment, aerospace, polar exploration, etc. that are difficult to charge, high energy density primary batteries have once again become the focus of people's attention. Therefore, it is of great significance to explore positive electrode materials with high energy density, high power density and excellent safety.

[0003] Currently, commercial lithium primary batteries include lithium-carbon fluoride (Li-CFx) batteries, lithium-sulfur dioxide (Li-SO2) batteries, lithium-thionyl chloride (Li-SOCl2) batteries, lithium-manganese dioxide (Li-MnO2) batteries, etc. Among them, lithium-carbon fluoride (Li-CFx) primary batteries are currently the chemical power source with the highest energy density, but their preparation requires fluorine gas (F2), which is highly toxic, has high energy consumption, and causes serious environmental pollution problems; the positive electrodes of Li-SO2 and Li-SOCl2 are gas or liquid, and the active substances are easy to leak during use, thus causing safety problems; the cost of MnO2 electrode materials is relatively low, but the overall energy density of the battery is low, and the low-temperature performance and output power need to be improved.

[0004] In addition, small organic molecules have few active reaction sites and a small conjugated structure that is easy to dissolve, which results in the battery capacity being unable to be further increased. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an application method of a multi-active point pyrene-based fused ring compound in a primary battery to solve the problems of low energy density, relatively low operating voltage, high production cost, high toxicity, safety to be improved, easy solubility of organic molecules, and poor conductivity of existing lithium primary battery positive electrode materials.

[0006] The technical solution for achieving the purpose of the present invention is:

[0007] The present invention provides an application method of a multi-active point pyrene-based condensed ring compound in a primary battery. The positive electrode is prepared by using the multi-active point pyrene-based condensed ring compound as a positive electrode active material, and the primary battery is assembled by using an alkali metal as a negative electrode and an electrolyte.

[0008] The multi-active point pyrene-based condensed ring compound is:

[0009]

[0010] The main component is pyrene with a condensed ring structure. By changing the reaction conditions to control the number of functional group substitutions, a series of condensed ring nitro compounds are obtained. Its condensed ring structure can enhance the π-π effect, improve the conductivity of the material, and have more reactive sites to increase the number of active functional groups, so that both the specific capacity and the discharge voltage are improved, thereby improving the energy density of the battery as a whole.

[0011] Furthermore, the synthesis method of the multi-active point pyrene-based condensed ring compound is: pyrene is dispersed in nitric acid, refluxed under heating and stirring conditions, and the multi-active point pyrene-based condensed ring nitro compound can be obtained by suction filtration, washing, and drying. According to different reaction conditions, positive electrode materials with different numbers of substitutions and nitro groups as active functional groups can be obtained.

[0012] Furthermore, the multi-active point pyrene-based condensed ring compound is in-situ loaded with conductive carbon during the synthesis process, and its preparation method is: dispersing pyrene in nitric acid, adding conductive carbon (the mass ratio of the added conductive carbon to the raw material pyrene is between 1:4-1:10), reflux reaction under heating and stirring conditions, and obtaining the in-situ carbon-loaded multi-active point pyrene-based condensed ring nitro compound through suction filtration, washing and drying.

[0013] Furthermore, the conductive carbon is one or more of graphene, Ketjen black and carbon nanotubes.

[0014] Furthermore, a solid multi-hydroxy proton-donating additive is added during the preparation of the positive electrode, and the preparation method is as follows: the multi-active point pyrene-based fused ring compound, conductive agent, binder, and solid multi-hydroxy proton-donating additive are uniformly mixed to form a uniform slurry, which is then scraped onto the current collector and dried to obtain a positive electrode sheet.

[0015] Furthermore, the conductive agent is preferably Super P, Ketjen black, or graphene, and the binder is preferably an aqueous binder such as sodium alginate SA, sodium carboxymethyl cellulose CMC, or polyacrylate PAA.

[0016] Furthermore, the solid polyhydroxy proton-donating additive is a polyhydroxy aldehyde or a polyhydroxy ketone, preferably one or more of glucose, fructose, galactose, mannose and ribose.

[0017] Furthermore, the added amount of the solid polyhydroxy proton-donating additive is 1% to 10% of the total mass of the positive electrode.

[0018] Furthermore, the electrolyte is a solution of lithium salt with a concentration of 0.3-5 mol / L; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium hexafluorophosphate LiPF6, lithium perchlorate LiClO4 or lithium tetrafluoroborate LiBF4; the solvent of the electrolyte is a mixed solution of chain ethers, cyclic ethers and cyclic carbonates in different proportions;

[0019] Furthermore, the electrolyte is 0.5M LiClO4 DME added with 10-20% FEC (V / V) as the electrolyte.

[0020] Furthermore, a liquid proton-donating additive is added to the electrolyte, and the added amount is 1% to 10% of the total mass of the electrolyte.

[0021] Furthermore, the liquid proton-donating additive is a compound containing hydroxyl or amino groups that can provide protons in an ionized state, including but not limited to water, methanol, ethanol, ethylene glycol, glycerol, ethylamine, ethylenediamine, amide compounds, etc.

[0022] With pyrene as the main body, the reaction active sites are increased while the conjugated structure is enlarged, which can not only improve the specific capacity of the battery but also improve the conductivity of the material. With nitro as the active group, it can increase the discharge capacity and also serve as an electron-pulling group to increase the discharge voltage, thereby improving the energy density of the battery as a whole.

[0023] Advantages and beneficial effects of the present invention:

[0024] (1) The present invention provides a method for applying a multi-active point pyrene-based condensed ring compound in a primary battery. The multi-active point pyrene-based condensed ring compound is a series of condensed ring aromatic compounds with pyrene as the main material, and the active functional group can be a nitro group with different numbers of substitutions. The pyrene-based main body increases the conjugated structure and can enhance the π-π effect and improve the conductivity of the material. The nitro group with different numbers of substitutions is used as the active group to improve the discharge capacity and can also serve as an electron-withdrawing group to increase the discharge voltage, thereby improving the energy density of the battery as a whole.

[0025] (2) The present invention achieves a significant improvement in the performance of multi-active site organic positive electrode materials in primary batteries by in-situ carbon loading of active substances, introduction of solid multi-hydroxy proton-donating additives and liquid proton-donating additives.

[0026] (3) The lithium organic primary battery assembled with the positive electrode material obtained according to the present invention has a specific capacity of more than 1400mAh / g and a specific energy of more than 3600Wh / kg, which exceeds the energy density of all organic electrode materials and most high-specific-energy inorganic electrode materials reported so far, and can be stored for a long time. In addition, the raw material cost is low, the synthesis method is simple, and mass production can be achieved, which has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Liquid chromatography-quadrupole time-of-flight mass spectrometry of mononitropyrene, dinitropyrene, trinitropyrene and tetranitropyrene prepared in Examples 1-4 provided by the present invention;

[0028] Figure 2 The discharge curve of a lithium primary battery assembled with mononitropyrene, dinitropyrene, trinitropyrene and tetranitropyrene prepared in Examples 1-4 provided by the present invention as positive electrode materials;

[0029] Figure 3 A discharge curve diagram of a lithium primary battery assembled with trinitropyrene in situ loaded on conductive carbon prepared in Examples 5-7 of the present invention and trinitropyrene prepared in Example 3 as positive electrode materials;

[0030] Figure 4 A discharge curve diagram of a lithium primary battery assembled with the positive electrode prepared in Example 8 of the present invention and the positive electrode prepared in Example 3 without adding glucose;

[0031] Figure 5 A discharge curve diagram of a lithium primary battery comparing the electrolyte of Example 9 provided by the present invention with the electrolyte of Example 3. DETAILED DESCRIPTION

[0032] The present invention will be further explained below through the accompanying drawings and specific examples. The following examples are only used as an illustration and should not be understood as limiting the scope of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0033] Example 1

[0034] The preparation method of mononitropyrene (1-NP) is as follows: a mixture of pyrene (1.00 g) and glacial acetic acid (30 mL) is added to a flask, the mixture is heated at 60°C to dissolve the pyrene, and a mixture of glacial acetic acid (5 mL) and concentrated nitric acid (0.49 g, nitric acid concentration 68%) is added dropwise under stirring, the mixture is stirred at room temperature for 4 hours, and then poured into ice water. The solid is filtered out, washed with deionized water and dried.

[0035] Preparation of positive electrode: Grind and mix nitropyrene with conductive carbon (Superp) and binder (sodium alginate) in a mass ratio of 6:3:1 and transfer to a homogenization box, add appropriate amount of deionized water. After fully mixing in a mortar and homogenizer, use a spatula to apply the slurry on aluminum foil, first dry it in a 60℃ forced air oven for 6 hours, and then dry it in a 60℃ vacuum oven for 12 hours. Use a tabletting machine to obtain a disc with a diameter of 10 mm, and quickly transfer it to a glove box with a high-purity argon atmosphere (O2<0.1ppm, H2O<0.1ppm) for standby.

[0036] Prepare electrolyte 0.5M LiClO4 DME (ethylene glycol dimethyl ether) + FEC (fluoroethylene carbonate) (FEC accounts for 20% of the electrolyte volume) in a glove box, use polypropylene (PP) diaphragm, model Celgard2400, lithium metal as negative electrode, use the above positive electrode, negative electrode, electrolyte (electrolyte dosage is 20μL) to assemble a button half-cell model CR2032 for electrochemical performance testing. Use the Blue Battery Test System to perform constant current charge and discharge tests with a current density of 20mA g -1 , the voltage test range is 3.0V-2.0V. The discharge curve is shown in Figure 2 .

[0037] Example 2

[0038] The preparation method of dinitropyrene (DNP) is as follows: add glacial acetic acid (25 mL) to pyrene (2.5 g), slowly add a mixture of concentrated nitric acid (1.9 mL nitric acid concentration 68%) and glacial acetic acid (5 mL), and stir the reaction mixture at 75°C for 1 hour. The reaction mixture was cooled to room temperature, the resulting precipitate was filtered, washed with ethanol, and dried in vacuo. The crude product contains a mixture of 1,6-dinitropyrene, 1,8-dinitropyrene, 1,3-dinitropyrene and 1-nitropyrene. The resulting mixture was separated by column chromatography to obtain a dinitropyrene product. The electrode was prepared in the same manner as in Example 1, the battery was assembled and tested, and the discharge curve is shown in FIG. Figure 2 .

[0039] Example 3

[0040] The preparation method of trinitropyrene (1,3,6-TNP) is as follows: grind pyrene (4 g) is added to concentrated nitric acid (320 mL nitric acid concentration 68%), refluxed and stirred at 80°C for 24 hours. After cooling to room temperature, the mixture is diluted with deionized water and filtered through a 0.22 μm microporous membrane for multiple washings to remove the acid. The electrode is prepared in the same manner as in Example 1, and the battery is assembled and tested. The discharge curve is shown in FIG. Figure 2 .

[0041] Example 4

[0042] The preparation method of tetranitropyrene (1,3,6,8-TNP) is as follows: crushed pyrene (1.5 g) is added to 25 (mL) fuming nitric acid cooled to 0°C, the suspension is stirred for 2 hours, then warmed to room temperature and stirred for 12 hours. The filtered mixture is washed with deionized water several times until neutral, centrifuged several times with dimethyl sulfoxide (DMSO), the dark filtrate is removed, the yellow powder is thoroughly washed with ethanol, and a bright yellow product is obtained after drying, and the product is obtained after vacuum drying. The electrode is prepared in the same manner as in Example 1, the battery is assembled and tested, and the discharge curve is shown in FIG. Figure 2 .

[0043] Example 5

[0044] Step 1: Add 40 mL of concentrated nitric acid (68%) to the ground pyrene (0.5 g) and Superp (0.1 g), reflux and stir at 80°C for 24 hours. After cooling to room temperature, dilute the mixture with deionized water and filter through a 0.22 μm microporous membrane for multiple washes to remove the acid. After the obtained product was dried at 60°C in vacuo for 12 hours, trinitropyrene loaded on Superp in situ was obtained.

[0045] Step 2: Calculate the carbon content according to the elemental analysis test results. The conductive carbon accounts for about 10% of the total mass of the product after loading. By calculation, the mass of the active substance in the obtained product and the total amount of the conductive carbon (Superp) and the binder (sodium alginate) are ground and mixed in a mass ratio of 6:3:1 and transferred to a homogenization box, dried in a 60°C blast oven for 6 hours, and then dried in a 60°C vacuum oven for 12 hours. A disc with a diameter of 10 mm is obtained by a tabletting machine. In an argon glove box, 0.5M LiClO4 DME with 20% FEC (V / V) is used as the electrolyte, Celgard 2400 is used as the diaphragm, and the above-mentioned in-situ carbon-loaded trinitropyrene positive electrode sheet and the metal lithium negative electrode are assembled into a button battery for the test of electrochemical performance. The test conditions are the same as above.

[0046] Example 6

[0047] The difference from Example 5 is that the Superp in step 1 is replaced by carbon nanotubes to obtain trinitropyrene in situ loaded on carbon nanotubes.

[0048] Example 7

[0049] The difference from Example 5 is that Superp in step 1 is replaced by graphene to obtain trinitropyrene in situ loaded on graphene.

[0050] Figure 3 The discharge curve of the lithium primary battery assembled with the trinitropyrene in situ loaded on the conductive carbon prepared in Examples 5-7 and the trinitropyrene prepared in Example 3 as positive electrode materials is shown in the figure. It can be seen from the figure that the discharge specific capacity of the trinitropyrene loaded on the in-situ carbon is significantly improved compared with that of the unloaded trinitropyrene. The carbon nanotubes in the trinitropyrene loaded on the in-situ carbon have the best performance, reaching 1272 mAh g -1 .

[0051] Example 8

[0052] Trinitropyrene (120 mg), Superp (60 mg), sodium alginate (20 mg), and glucose (20 mg) prepared in Example 3 were fully ground in a mortar at a mass ratio of 6:3:1:1 and transferred to a homogenization box. An appropriate amount of deionized water was added to mix to form a uniform slurry, and then applied to the current collector, dried in a 60°C blast oven for 6 hours, and then dried in a 60°C vacuum oven for 12 hours. A disc with a diameter of 10 mm was obtained by a tabletting machine to obtain a positive electrode sheet with a proton-donating additive introduced with a solid polyhydroxy compound. In an argon glove box, 0.5MLiClO4 DME with 20% FEC (V / V) was used as an electrolyte, and Celgard2400 was used as a diaphragm. The positive electrode sheet with the solid polyhydroxy proton-donating additive introduced above was assembled with a metal lithium negative electrode into a button battery for the test of electrochemical performance, and the test conditions were the same as above. Figure 4 The figure shows the discharge curves of lithium primary batteries assembled with positive electrodes prepared with and without glucose. It can be seen from the figure that the discharge capacity and discharge voltage of the positive electrode with added glucose are improved compared with those without glucose. Glucose, as a solid proton donor additive, can interact with the active material on the positive electrode side to increase its discharge voltage and provide a certain amount of protons in the nitro reduction process.

[0053] Example 9

[0054] The difference from Example 3 is that the electrolyte of the assembled battery is different. The electrolyte is: 0.5M LiClO4DME added with 20% FEC and 5% ethylene glycol (V / V) for electrochemical performance testing. Figure 5 It can be seen that the electrolyte with ethylene glycol added exhibits better electrochemical performance than the original electrolyte, with a discharge capacity of 1301 mAh g -1 As a liquid proton-donating additive, ethylene glycol has a significant effect on improving the electrochemical performance of primary batteries.

[0055] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A method for applying a multi-active-point pyrene-based fused-ring compound in a primary battery, characterized in that: The positive electrode is prepared by using a multi-active point pyrene-based condensed ring compound as a positive electrode active material, an alkali metal is used as a negative electrode, and a primary battery is assembled with an electrolyte. The multi-active point pyrene-based condensed ring compound is:

2. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 1, characterized in that: The synthesis method of the multi-active point pyrene-based condensed ring compound is as follows: pyrene is dispersed in nitric acid, refluxed under heating and stirring conditions, and the multi-active point pyrene-based condensed ring nitro compound is obtained by suction filtration, washing and drying.

3. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 2, characterized in that: The multi-active point pyrene-based condensed ring compound is in-situ loaded with conductive carbon during the synthesis process, and its preparation method is: pyrene is dispersed in nitric acid, conductive carbon is added, reflux reaction is carried out under heating and stirring conditions, and the multi-active point pyrene-based condensed ring nitro compound loaded with in-situ carbon can be obtained through suction filtration, washing and drying.

4. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 3, characterized in that: The conductive carbon is one or more of graphene, Ketjen black and carbon nanotubes.

5. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 1, characterized in that: A solid multi-hydroxy proton-donating additive is added during the preparation of the positive electrode. The preparation method is as follows: the multi-active point pyrene-based condensed ring compound, conductive agent, binder, and solid multi-hydroxy proton-donating additive are uniformly mixed to form a uniform slurry, which is then scraped onto a current collector and dried to obtain a positive electrode sheet.

6. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 5, characterized in that: The solid polyhydroxy proton-donating additive is polyhydroxy aldehyde or polyhydroxy ketone.

7. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 6, characterized in that: The polyhydroxy aldehyde or polyhydroxy ketone is one or more of glucose, fructose, galactose, mannose and ribose.

8. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 7, characterized in that: The added amount of the solid polyhydroxy proton-donating additive is 1% to 10% of the total mass of the positive electrode.

9. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 1, characterized in that: A liquid proton-donating additive is added to the electrolyte, and the added amount is 1% to 10% of the total mass of the electrolyte.

10. The method for applying the multi-active-point pyrene-based fused-ring compound in a primary battery according to claim 9, characterized in that: The liquid proton-donating additive is one or more of water, methanol, ethanol, ethylene glycol, glycerol, ethylamine, ethylenediamine, and amide compounds.

Citation Information

Patent Citations

  • Method for preparing lithium ionic battery anode material spherical LiFePO4 / C

    CN101330141A

  • Aromatic condensed ring quinones compound positive pole material for one-class lithium secondary battery

    CN103022496A

  • Preparation method for amino functional graphene quantum dot / carbon nanotube / carbon cloth three-dimensional flexible electrode

    CN106653384A

  • Nitric acid modified porous carbon and applications thereof

    CN107694515A

  • Lithium ion battery organic positive electrode material and application thereof

    CN110429279A

Cited By

  • Electron supplement agent, preparation method, alkali metal battery and application

    CN121983606A

  • An electron supplement agent, its preparation method, an alkali metal battery, and its application.

    CN121983606B